Non-canonical inflammasome activation of caspase-4/caspase-11 mediates epithelial defenses against enteric bacterial pathogens - Knodler, Leigh A. (2014)
Inflammasome-mediated host defenses have been extensively studied in innate immune cells. Whether inflammasomes function for innate defense in intestinal epithelial cells, which represent the first line of defense against enteric pathogens, remains unknown. We observed enhanced Salmonella enterica serovar Typhimurium colonization in the intestinal epithelium of caspase-11 deficient mice, but not at systemic sites. In polarized epithelial monolayers, siRNA-mediated depletion of caspase-4, a human orthologue of caspase-11, also led to increased bacterial colonization. Decreased rates of pyroptotic cell death, a host defense mechanism that extrudes S. Typhimurium infected cells from the polarized epithelium, accounted for increased pathogen burdens. The caspase-4 inflammasome also governs activation of the proinflammatory cytokine, interleukin (IL)-18, in response to intracellular (S. Typhimurium) and extracellular (enteropathogenic Escherichia coli) enteric pathogens, via intracellular LPS sensing. Therefore an epithelial cell intrinsic non-canonical inflammasome plays a critical role in antimicrobial defense at the intestinal mucosal surface.